Diseño de un Sistema Fotovoltaico para Abastecer Parcialmente de Energía eléctrica un conjunto residencial ubicado al sur de Bogotá, Colombia - Saavedra Cotrina, Deiver (TECCIENCIA, 2022)
The Torres de Bellavista residential complex has 1,500 apartments, distributed in five towers of thirty floors each, a nine-story building for approximately 750 parking spaces and other community infrastructure. Given the dimensions of this set, it is presumed that electricity consumption entails high economic and environmental costs, so one way to solve this cost is the use of alternative, non-conventional methods of electricity generation, for this reason, it is proposed to design a photovoltaic system that allows partial supply of electricity to the common and administrative areas of the residential complex. The calculations of the components of the photovoltaic system were carried out using the methodology of the worst month, which consists of finding the month in which the relationship between solar irradiation and electricity consumption makes it more difficult to satisfy the energy demand; When making the design under these conditions, it will be guaranteed that the rest of the year an electricity supply greater than the month of the calculations will be achieved. This methodology made it possible to demonstrate that, with the installation of 100 photovoltaic solar panels distributed on the roofs of the 5 towers and connected to the supply network, it is possible to satisfy up to 27% of the energy demand of the common areas. To achieve the objective of this proposal, an initial investment of COP 220,453,967 must be made, of which 50% must be financed by a bank. However, the investment can be recovered between 5 and 6 years after implementation, starting to generate returns for the rest of the estimated useful life of 25 years. The benefits of implementing this proposal are not only economic but also environmental, since it manages to reduce Greenhouse Gas-GHG emissions by 37.07 CO2e for the first year of implementation.